SON-1210 - a novel bifunctional IL-12 / IL-15 fusion protein that improves cytokine half-life, targets tumors, and enhances therapeutic efficacy - Cini, John K.; Dexter, Susan; Rezac, Darrel J.; McAndrew, Stephen J.; Hedou, Gael; Brody, Rich; Eraslan, Rukiye-Nazan; Kenney, Richard T.; Mohan, Pankaj (Frontiers in Immunology, 2023)
Background: The potential synergy between interleukin-12 (IL-12) and IL-15 holds promise for more effective solid tumor immunotherapy. Nevertheless, previous clinical trials involving therapeutic cytokines have encountered obstacles such as short pharmacokinetics, limited tumor microenvironment (TME) targeting, and substantial systemic toxicity. Methods: To address these challenges, we fused single-chain human IL-12 and native human IL-15 in cis onto a fully human albumin binding (FHAB) domain single-chain antibody fragment (scFv). This novel fusion protein, IL12-FHAB-IL15 (SON-1210), is anticipated to amplify the therapeutic impact of interleukins and combination immunotherapies in human TME. The molecule was studied in vitro and in animal models to assess its pharmacokinetics, potency, functional characteristics, safety, immune response, and efficacy. Results: SON-1210 demonstrated robust binding affinity to albumin and exhibited the anticipated in vitro activity and tumor model efficacy that might be expected based on decades of research on native IL-12 and IL-15. Notably, in the B16F10 melanoma model (a non-immunogenic, relatively “cold” tumor), the murine counterpart of the construct, which had mouse (m) and human (h) cytokine sequences for the respective payloads (mIL12-FHAB-hIL15), outperformed equimolar doses of the co-administered native cytokines in a dose-dependent manner. A single dose caused a marked reduction in tumor growth that was concomitant with increased IFNγ levels; increased Th1, CTL, and activated NK cells; a shift in macrophages from the M2 to M1 phenotype; and a reduction in Treg cells. In addition, a repeat-dose non-human primate (NHP) toxicology study displayed excellent tolerability up to 62.5 µg/kg of SON-1210 administered three times, which was accompanied by the anticipated increases in IFN levels. Toxicokinetic analyses showed sustained serum levels of SON-1210, using a sandwich ELISA with anti-IL-15 for capture and biotinylated anti-IL-12 for detection, along with sustained IFNγ levels, indicating prolonged kinetics and biological activity. Conclusions: Collectively, these findings support the suitability of SON-1210 for patient trials in terms of activity, efficacy, and safety, offering a promising opportunity for solid tumor immunotherapy. Linking cytokine payloads to a fully human albumin binding domain provides an indirect opportunity to target the TME using potent cytokines in cis that can redirect the immune response and control tumor growth.